Ice Breaking dalam Pembelajaran: Meningkatkan Minat Belajar Siswa pada Materi Pendidikan Agama Kristen - Gulo, Betieli; Gulo, Rayani Arnidar; Zai, Anugerah Jaya; Hia, Sesilia; Gulo, Liami (Sekolah Tinggi Teologi Sumatera Utara, 2024)
The average attention span of students in the process of teaching and learning activities in class is between ten and twenty minutes. After that, the teacher reacts to being sleepy, disturbing friends, being busy with his own activities, going in and out of class and sometimes finding it difficult to return to a conducive state. This problem is very serious and has the potential to reduce students' interest in learning about Christian Religious Education subject matter. The Ice breaking learning strategy is able to change a passive atmosphere into an active one. This strategy can be used by teachers to increase students' interest in receiving the material presented. This research aims to determine the effectiveness of the ice breaking learning strategy in increasing students' interest in learning and returning students' attention to Christian Religious Education material. This research uses qualitative research based on library research. Researchers search for and analyze research in the form of journals, proceedings, books and other articles related to the research title and then write them down as research results. From the results of the analysis, it was found that the application of the ice breaking learning strategy was able to develop and optimize students' brains and creativity, train them to think systematically to solve problems and increase their self-confidence. Therefore, teachers need to carefully consider using the ice breaker learning method and choose the type of ice breaker used based on the principles of motivation, synchronization, appropriate situation, and does not contain elements of SARA and pornography. AbstrakRata-rata rentang perhatian naradidik dalam proses kegiatan belajar mengajar di kelas antara sepuluh sampai dua puluh menit. Setelah itu, reaksi mengantuk, mengganggu teman, sibuk pada kegiatan sendiri, keluar masuk kelas ditemui guru dan terkadang sulit dikembalikan pada keadaan yang kondusif. Permasalahan ini sangat serius dan berpotensi mengurangi minat belajar siswa pada materi pelajaran pendidikan agama Kristen. Strategi belajar ice breaking mampu mengubah suasana yang pasif menjadi aktif. Strategi ini dapat digunakan oleh guru dalam meningkatkan minat siswa untuk menerima materi yang disampaikan. Penelitian ini bertujuan mengetahui efetivitas strategi belajar ice breaking dalam meningkatkan minat belajar siswa serta mengembalikan perhatian siswa pada materi pendidikan agama Kristen. Penelitian ini menggunakan penelitian kualitatif berbasis library research. Peneliti mencari dan menganalisis litertur penelitian dalam bentuk jurnal, prosiding, buku, dan artikel lainnya yang berkaitan dengan topik yang diteliti. Dari hasil analisis ditemukan bahwa penerapan strategi pembelajaran ice breaking mampu mengembangkan dan mengoptimalkan kemampuan berpikir dan kreatifitas siswa, melatih berfikir sistematis untuk memecahkan masalah serta dapat meningkatkan rasa percaya diri. Oleh karena itu, guru perlu mempertimbangkan dengan matang untuk menggunakan metode pembelajaran ice breaking dan memilih jenis ice breaking yang digunakan berdasarkan prinsip motivasi, sinkronisasi, tepat situasi, dan tidak mengandung unsur SARA dan pornografi.